Bioconcentration and desorption kinetic of potentially toxic elements in soils cultivated with horticultural crops in organic and conventional systems - Eloá Moura Araujo (2018)
Potentially toxic elements (PTEs) can be absorbed and accumulated in vegetables organ and tissues, and this is an important channel through which PTEs can enter into the food chain. Soil management may interfere in the behavior of PTEs in the system. So, the study of the dynamics of elements in the soil is fundamental to a better understanding of factors that influence soil-plant transfer. In the state of Pernambuco, Brazil, the production of vegetables is mainly concentrated in small or medium organic and conventional farms located in the Agreste and Sao Francisco regions. Our aims in this research were: i) to determine the contents of PTEs in soil and in vegetables produced under conventional and organic systems in garden soils of Pernambuco; ii) to investigate the forms of the PTEs and their uptake by the vegetables based on different soil-plant transfer factors; iii) to use the calculated transfer factors to assess the human risk exposure; iv) to assess the effect of aging and organic matter (OM) on copper (Cu) desorption in garden soils; v) to determine if manure application to soils increases water soluble Cu concentrations; and vi) to verify the efficiency of machine learning techniques in the classification of vegetables produced under organic and conventional systems. Acid and complexing solutions were employed to extract total contents of PTEs in plants and to extract pseudototal, reactive and bioavailable fractions of the PTEs in soils. Soil-plant transfer factors and human risk assessment were calculated based on the determined levels of PTEs. Kinetic assays were developed using rates of organic composts added to Cu-spiked soils to model the Cu desorption. Water extractable Cu and dissolved organic carbon (DOC) were extracted from soils amended with dairy manure, and the Cu-DOC interactions were studied using spectroscopic techniques. Lettuce (Lactuca sativa) leaves had the highest capacity to accumulate PTEs; conventional system promoted higher PTEs values in soils and plants than the organic production; regardless of the scenario, children and adults in contact to vegetables cropped in organic system have a lower health risk than individuals exposed to lettuce leaves conventionally produced. The addition of OM promoted greater Cu desorption, while aging lead to a reduction in the Cu release. The Fouriertransform infrared spectroscopy spectra showed increase in the presence of aliphatic and carboxylic groups in the extracts from the manure-amended soils. Carboxylic acid functional groups on the DOC formed strong bonds with Cu, which can promote Cu transport as dissolved Cu-organic complexes in the soil profile. The Support Vector Machine had an accuracy over 90% to classify the vegetables in the two groups (organic and conventional); and this high assertiveness rate highlights the potential of using elemental quantification and algorithms as support techniques in the process of authenticity and inspection of organic products.